2022
DOI: 10.1007/s10551-022-05111-3
|View full text |Cite
|
Sign up to set email alerts
|

A Critique of Vanishing Voice in Noncooperative Spaces: The Perspective of an Aspirant Black Female Intellectual Activist

Abstract: We adopt and extend the concept of ‘noncooperative space’ to analyze how (aspirant) black women intellectual activists attempt to sustain their efforts within settings that publicly endorse racial equality, while, in practice, the contexts remain deeply racist. Noncooperative spaces reflect institutional, organizational, and social environments portrayed by powerful white agents as conducive to anti-racism work and promoting racial equality but, indeed, constrain individuals who challenge racism. Our work, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 108 publications
(193 reference statements)
0
5
0
Order By: Relevance
“…I subsequently illustrate the above stated point by reflecting on my collaborative autoethnography concerning how I suffered a racially aggravated domestic assault, and was temporarily 'homeless' at the height of a teaching term and the Covid-19 pandemic (Muzanenhamo, & Chowdhury, 2022). I proceed by addressing the paradox of fear and freedom against the backdrop of hope in the sections that I have identified below as: The first timefloodgates opened; Trembling like a reed -The revise and resubmit process, and; the Acceptance -What a dreadful world.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…I subsequently illustrate the above stated point by reflecting on my collaborative autoethnography concerning how I suffered a racially aggravated domestic assault, and was temporarily 'homeless' at the height of a teaching term and the Covid-19 pandemic (Muzanenhamo, & Chowdhury, 2022). I proceed by addressing the paradox of fear and freedom against the backdrop of hope in the sections that I have identified below as: The first timefloodgates opened; Trembling like a reed -The revise and resubmit process, and; the Acceptance -What a dreadful world.…”
Section: Introductionmentioning
confidence: 93%
“…When I sat down for the first time to write about how I had been physically assaulted by a white female housemate that I had invited into my rented home (see Muzanenhamo, & Chowdhury, 2022), I felt immensely relieved. Such relief embodied freedom and it was (temporarily) liberating.…”
Section: The First Time -Floodgates Openedmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit bias occurs when prejudices and stereotypes are (un)intentionally perpetuated (Greenwald & Banaji, 1995;Levy, 2012). Researchers have long suggested that such implicit biases are institutionalized (Banks & Ford, 2009;Medina, 2012) and skew normative views in a particular way (e.g., Ghoshal, 2005;Muzanenhamo & Chowdhury, 2022Willmott, 2011). Breaking free from such epistemic biases is difficult (Medina, 2012) because, often, identity and dignity violations of MSs are normalized and become embedded into social structures.…”
Section: Limitations Of Stakeholder Theory In Relation To Ms Conceptu...mentioning
confidence: 99%
“…This subsequently limits adequate representation of these groups in academic work (not only publications, but also various disseminating mediums, such as teaching, consultancy, and conferences). Such misrepresentation processes are then normalized over time in academic discourse, either in the absence of authentic accounts or voices (Alves, 2013;Muzanenhamo & Chowdhury, 2022a), or because the marginalized group could not find a fair and proportionate opportunity to contradict and challenge their misrepresentation by the researchers (Cruz, 2014;Mudimbe, 1988;Muzanenhamo & Chowdhury, 2022b). In the latter case, even if researchers have access to marginalized groups, they may choose to interview members without due diligence (e.g., without capturing the special situation and circumstances of marginalized groups) and, thus, perpetuate epistemic neocolonialism (Muhammad et al, 2015).…”
Section: Introductionmentioning
confidence: 99%